Pengaruh Penerapan Literasi Digital dan Gaya Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PAI - Ulya, Shifatul (IJIT: Indonesian Journal of Islamic Teaching, 2024)
ABSTRACT Along with the paradigm shift in 21st-century education, which is inseparable from information and communication technology, the relationship between digital literacy as a basic literacy skill and students' learning outcomes in Islamic Education subjects needs to be examined. Learning style is one of the factors that influence learning outcomes. Understanding an individual's learning style can determine a more effective learning approach. When the learning process becomes easier and more effective, the learning outcomes will also be better. The results of this study show a positive and significant influence of both digital literacy implementation and learning styles on students' learning outcomes. Partially, digital literacy significantly influences learning outcomes with a t-value of 6.718 > t-table 1.917. Visual learning style (X2.1) significantly influences learning outcomes with a t-value of 5.906 > t-table 1.917. Auditory learning style (X2.2) significantly influences learning outcomes with a t-value of 6.969 > t-table 1.917. However, the kinesthetic learning style (X2.3) has a t-value of -0.690, smaller than t-table 1.917, and a significance value of 0.491, greater than the significance threshold of 0.05. Thus, H0 is accepted, meaning that kinesthetic learning style does not significantly influence students' learning outcomes. Keywords: Digital Literacy, Learning Style, Learning Outcomes